Mapping radiative cooling potential for africa under different climate change scenarios - Monterrubio, Jesús; Vilà, Roger; Medrano, Marc; Martorell, Ingrid; Castell, Albert (Frontiers in Environmental Science, 2026)
Africa, with a significant portion of its territory located within the tropical latitudes, experiences high cooling demands. Addressing these requirements in a renewable way is possible thanks to Radiative Cooling (RC). RC utilizes the atmospheric window from 8 to 13 µm to emit radiation to outer space, enabling the achievement of sub-ambient temperatures. A Kriging geospatial interpolation method is applied in this work to develop maps of RC potential, considering broadband emitters, for the typical meteorological year from 1991 to 2010 and predictions for 2030–2050 based on future emissions scenarios of the Intergovernmental Panel on Climate Change. A comparison is made between nighttime and all-day RC potential. The results reveal that all-day RC power potential is at least 22% higher than nighttime potential, while in terms of energy, the difference exceeds 156%. No significant variation is observed among future emissions scenarios. The average nighttime RC power potential exceeds 70 W⋅m−2, while the average all-day potential surpasses 87 W⋅m−2. Mean values for the nighttime RC energy potential are above 294 kWh·m-2, while all-day results are over 763 kWh·m-2. The potential of RC in many regions of Africa is promising and these maps will be a useful resource to estimate this RC potential.